Protocol to design techniques for implementing software development best practices (2015)
Software engineering best practices allow significantly improving the software development. However, the implementation of best practices requires skilled professionals, financial investment and technical support to facilitate implementation and achieve the respective improvement. In this paper we proposes a protocol to design techniques to implement best practices of software engineering. The protocol includes the identification and selection of process to improve, the study of standards and models, identification of best practices associated with the process and the possible implementation techniques. In addition, technical design activities are defined in order to create or adapt the techniques of implementing best practices for software development.